Des promenades parisiennes d’un immigré hongrois ou les descriptions de Paris de Gyula Illyés - Benda, Mihály (Verbum – Analecta Neolatina, 2008)
Gyula Illyés, Hungarian poet, fiction writer, essayist and dramatist, emigrated to Paris after the fall of the Hungarian Republic in 1919. There, he came into contact with the working class movement as well as with surrealistic circles. Strongly influenced by modern French writing, Illyés nevertheless adopted realism in his novels. He reflects upon his emigration times in Paris in his novel, Hunok Párisban [Huns in Paris]. The present paper focuses on the following main issues in relation to this novel: types of description, panoramic views, walks, atmosphere of certain districts, the stylistic characteristics of the descriptive sequences. Illyés’s description of Paris is a classic example of a type of urban literature that was pioneered in Paris of the 1840s, and was used to celebrate the diversity and dynamismof themodern city. At the center of his description was the figure of the flâneur, or urban stroller, who embodied and represented the quintessential qualities of urban modernity.